Memory and desire : a novel - Caputo, Philip (Arcade Publishing, 2023)
When he discovers stranded Cuban refugees during a fishing outing turned tragedy, newsman Luke Blackburn becomes the center of a media firestorm that threatens to blow up his marriage while his star investigative reporter slowly pieces together a story of corruption and cartel money in his refuge, Key West.